2011
DOI: 10.1111/j.1600-0765.2011.01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L‐ascorbic acid 2‐phosphate magnesium salt on the properties of human gingival fibroblasts

Abstract: These results suggest that APM is more effective than AsANa in terms of intake, collagen synthesis, decreasing cell damage and inhibiting interleukin-8 expression in human gingival fibroblasts. This suggests that local application of APM can help to prevent periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 45 publications
2
33
0
5
Order By: Relevance
“…In addition, Tsutsumi et al . reported that APM was more effective in terms of intake and suppressive effect on intracellular ROS in human gingival fibroblasts. These results suggest that the poor permeability of VC into epi‐4 cells is the cause of VC ineffectiveness.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Tsutsumi et al . reported that APM was more effective in terms of intake and suppressive effect on intracellular ROS in human gingival fibroblasts. These results suggest that the poor permeability of VC into epi‐4 cells is the cause of VC ineffectiveness.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, total levels of ROS or antioxidant activity were determined using fluorescence analysis (Tsutsumi et al. ), chemiluminescence (Ginsburg et al. ), and absorptiometry (Tamaki et al.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with worse periodontal condition tended to have increased oxidative injury to periodontal tissue. Recently, total levels of ROS or antioxidant activity were determined using fluorescence analysis (Tsutsumi et al 2012), chemiluminescence (Ginsburg et al 2013), and absorptiometry (Tamaki et al 2011). However, these analyses quantify antioxidant activities against nonspecific ROS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Melsmon contains a variety of vitamins, which improve the production capabilities of collagen in HGFs 27) . When considering these points, we believe that the growth factors and vitamins in Melsmon can probably act to improve the collagen production by HGFs.…”
Section: Discussionmentioning
confidence: 99%